Peran Penyuluh Agama Islam dalam Membangun Moderasi Beragama Berbasis Literasi pada Era Media Baru 5.0 di Kabupaten Majalengka - Susanto, Agus; Ulfah, Maya (Islamic Extension Guidance Study Program (BPI) of the Faculty of Da'wah and Communication, 2022)
Abstract: This study is aimed to determine several strategic alternatives by maximizing the role of counsellor of Islam in developing religious moderation based on literacy in the new media era of 5.0 in Majalengka Regency. In this study, the author used a mixed methodology, a methode that combine qualitative and quantitative approaches and used a SWOT analysis as a knife analysis to examine internal and external factors that influence the counsellor of Islam in developing religious moderation based on literacy in the new media era of 5.0 in Majalengka Regency. Based on the results of IFAS-EFAS, it is discovered that the role of counsellor of Islam in developing religious moderation based on literacy in the new media era of 5.0 in Majalengka Regency is relatively good and must be maintained because it has enormous potential for public benefit. The existing internal and external factors basically becomes a big support for the role of the counsellor of Islam.Abstrak: Tujuan penelitian ini adalah untuk menentukan berbagai alternatif strategis dengan memaksimalkan peran Penyuluh Agama Islam dalam membangun moderasi beragama berbasis literasi di Era Media Baru 5.0 di Kabupaten Majalengka. Penelitian ini menggunakan metode penelitian campuran (mixed methodology), metode yang memadukan pendekatan kualitatif dan kuantitatif dan menggunakan analisis SWOT sebagai pisau analisis untuk mengkaji faktor-faktor internal dan faktor-faktor eksternal yang mempengaruhi Penyuluh Agama Islam dalam membangun moderasi beragama berbasis literasi di Era Media Baru 5.0 di Kabupaten Majalengka. Berdasarkan hasil IFAS-EFAS, diketahui bahwa peran Penyuluh Agama Islam dalam membangun moderasi beragama berbasis literasi di Era Media Baru 5.0 di Kabupaten Majalengka sedah relatif baik dan harus dipertahankan karena memiliki potensi yang sangat besar untuk kemaslahatan publik. Keberadaan faktor-faktor internal dan eksternal, pada dasarnya, menjadi dukungan yang sangat besar bagi peran Penyuluh Agama Islam.